Nontrivial periodic solutions of a nonautonomous system of second-order differential equations - Terekhin, M. T. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We prove theorem, in which basic conditions for the existence of nontrivial periodic solutions are formulated in terms of the properties of the elements of the matrix of a linear approximation to a system.